PELATIHAN CARA MEMBUAT SABUN CUCI PIRING DARI MINYAK JELANTAH (MINYAK GORENG BEKAS) - diana, nurdiana; Susanti, Emilia; Afrizal, Afrizal; Roswati, Roswati (Universitas Islam Negeri Sultan Syarif Kasim Riau, 2024)
The cooking oil consumption has increased which has an impact in increasing cooking oil waste. This data is from the Central Statistics Agency. The characteristics of cooking oil damage like having bad smell and dark color. The objectives of this activity were: 1) To know the process of training in producing dish soap from used cooking oil; 2) To know the increasing knowledge of community in making dish soap from used cooking oil. The implementation method used the Participatory Action Research (PAR) Model. As a result of the activity, it can be seen in the details of the community service activities as follows: To know: identifying problems in making dish soap from used cooking oil; To Plan, planning actions by reviewing plans from various relevant sources such as books and community service articles to solve problems with the most effective and efficient solutions; To Act: implementing the plan that has been planned in the previous step; To reflect, evaluating the actions that have been taken to be reflected on the activities. In addition, the participants who have participated were able to understand well and clearly about the negative impacts caused by the repeated use of used cooking oil in terms of human health. Furthermore, the participants also understood the positive impacts of utilizing used cooking oil, such as making dishwashing soap that has economic value.